Development of a multi-axial mechatronic strength training and testing device - Raschner, C.; Patterson, C.; Barth, M.; Barth, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Strength and power are very important in elite sport so high quality training and testing is imperative. Mechatronic systems utilizing mechanical, electronic and software components are commonplace in industry. Published documentation of robotic applications in elite sport is rare, with the exception of isokinetic devices (Haddadina et al., 2009). The aim of this project was to develop a multi-axial mechatronic-based leg strength training and testing device. Methods: The following demands in the development process of the new device must be met: linear and curvilinear movements, variable speeds, bilateral and unilateral training, concentric and eccentric as well as sport-specific training. The athlete should have force and position visual feedback and a test mode should be available for all movements. Results: The developed device (Evo) is constructed as a right/left leg independent system, each consisting of two synchronized servomotors for the horizontal and vertical plane connected to spindles and servo controllers. The Evo operates with a programmable logic controller (PLC) used for automation of electromechanical input and output processes. Training and testing software are downloaded onto the PLC. The coach operates the Evo with a handheld terminal with a 6.5" VGA TFT display. The prototype allows for both single axis (horizontal and vertical linear movement) and for two coordinated axes (curves, circles and ellipses) training and testing. The maximum speeds of horizontal and vertical movements are 2.5m/s and 3.3m/s, respectively. Maximum load capacities are 4.8kN horizontally and 1.6kN vertically. The form of the ellipse (steeper or flatter angle) or circle as well as the repetitions per minute (up to 100) can be chosen on the handheld control. Additionally several stretch shortening cycles or stochastic shocks can be included. To measure the force values two 3-dimensional force plates were integrated into the foot plates. Discussion: The Evo utilizes mechatronics allowing a multitude of general and sport-specific movement combinations of concentric and eccentric exercises for leg/hip extension and flexion muscles with visual force and position feedback. Training and testing on the Evo offer basic research opportunities such as the analysis of stretchshortening cycles and stochastic shocks in the different training modes and speeds. Additionally eccentric hamstring training on the Evo in the vertical plane and with curves could have potential for injury prevention. Mechatronics can transform training conceptions into reality for high performance athletes.